"Time Management" as a Pattern for Improvingthe Work Effectiveness of Christian Leaders - Lestari, Ana; Ika Agustin, Eudia Anggelia; Daliman, Muner; Ming, David (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
The statement that "Time is money" is an unwise statement. The old Chinese proverb says "an inch of time equals an inch of gold is worth, but an inch of gold cannot replace an inch of time." The fundamental solution to the problem of time is: What is meant by time? What about time management? How wise is the basis for the process of managing time? How is wise time management as an exemplary pattern for Christian leaders in increasing work effectiveness? Answer: (1) Time never stops and it keeps flowing unstoppable. Time is all the events that occur in the life of every human being. (2) Time management is the management of time as effectively as possible for a person's life in accordance with his life goals, which include: taking care, organizing his life properly, considering which things are important, and which are not important. (3) Wisdom is being obedient to the corridor. Fear of God and his life is always under His guidance. Wisdom is only obtained by relating to God and reading His Word, because through the Word and practiced in daily life it will make people wisely.